2021
DOI: 10.1080/20442041.2021.1924538
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes of regional lake hydrologic characteristics in response to 21st century climate change

Abstract: Inland lakes are socially and ecologically important components of many regional landscapes. Exploring lake responses to plausible future climate scenarios can provide important information needed to inform stakeholders of likely effects of hydrologic changes on these waterbodies in coming decades. To assess potential climate effects on lake hydrology, we combined a previously published spatially explicit, processed-based hydrologic modeling framework implemented over the lake-rich landscape of the Northern Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is anticipated that subsequent simulations, especially those that will evaluate changes in lake biogeochemistry, will abandon this simplification and contribute to crosssectorial collaborations. On a regional scale, coupled hydrologic and lake model simulations to evaluate changes in lake water level (Hanson et al, 2021) and biogeochemistry (Zwart et al, 2019) for 3692 lakes in northern Wisconsin and Michigan have already been developed. Such regional studies can serve as a model for future cross-sectorial simulation in the ISIMIP.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…It is anticipated that subsequent simulations, especially those that will evaluate changes in lake biogeochemistry, will abandon this simplification and contribute to crosssectorial collaborations. On a regional scale, coupled hydrologic and lake model simulations to evaluate changes in lake water level (Hanson et al, 2021) and biogeochemistry (Zwart et al, 2019) for 3692 lakes in northern Wisconsin and Michigan have already been developed. Such regional studies can serve as a model for future cross-sectorial simulation in the ISIMIP.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Regional studies assessing the hydrologic responses of lakes to an ensemble of future climate change scenarios show that our omission might variably affect lakes depending on lake type and future climate outcomes for seasonal drying and wetting (Hanson et al, 2021;Hunt et al, 2013). These studies found that drainage lakes in northern Wisconsin, United States, which are hydrologically mediated by lake inflows and outflows, were projected to maintain stable water levels because of competing climatological factors that did not promote a clear drying trend.…”
Section: Water Balancementioning
confidence: 99%
“…Climate change is well documented around the globe (Karl and Trenberth 2003 ;Fawzy et al 2020 ;Chen et al 2021 ). It is anticipated to have effects such as changes in water temperature, lake levels, hydrologic extremes, fi sh species interactions, and harmful algal bloom frequency in waterbodies throughout the United States (Mulholland et al 1997 ;Tohver et al 2014 ;Chapra et al 2017 ;Miranda et al 2020 ;Hanson et al 2021 ) and elsewhere (Vörösmarty et al 2000 ;Woolway and Merchant 2019 ;Ashton et al 2022 ). A warming climate is of great concern for fi sheries professionals because increased water temperatures threaten coldwater species (McCullough et al 2009 ), including those targeted by recreational and commercial fi sheries and species that help to maintain ecological integrity (Isaak et al 2012 ;Lee et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is well documented around the globe (Karl and Trenberth 2003; Fawzy et al 2020; Chen et al 2021). It is anticipated to have effects such as changes in water temperature, lake levels, hydrologic extremes, fish species interactions, and harmful algal bloom frequency in waterbodies throughout the United States (Mulholland et al 1997; Tohver et al 2014; Chapra et al 2017; Miranda et al 2020; Hanson et al 2021) and elsewhere (Vörösmarty et al 2000; Woolway and Merchant 2019; Ashton et al 2022). A warming climate is of great concern for fisheries professionals because increased water temperatures threaten coldwater species (McCullough et al 2009), including those targeted by recreational and commercial fisheries and species that help to maintain ecological integrity (Isaak et al 2012; Lee et al 2020).…”
Section: Introductionmentioning
confidence: 99%